Effects of corneal surface morphology and tear-film with different locations of incision under the guided by corneal topography after phacoemulsification - Jie-Ying Yao (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM:To analyze the effects of corneal surface morphology and tear-film with different incisions guided by corneal topography after phacoemulsification.METHODS: Retrospective study. Totally 56 patients(60 eyes)were selected and divided into clear corneal incision group and angle scleral margin incision group who were treated by phacoemulsification in our hospital from June 2019 to December 2020. Best corrected visual acuity(BCVA), ocular surface disease index(OSDI)questionnaire, tear film break-up time(TBUT), corneal surface regularity index(SRI), corneal surface asymmetry index(SAI)and corneal surface astigmatism(CYL)were measured preoperatively and postoperatively, the results were statistically analyzed.RESULTS: BCVA in both groups increased after operation(P<0.01). The OSDI score of the two groups increased significantly after surgery(P<0.01). TBUT was shortened to varying degrees after surgery(P<0.05). SAI and SRI increased to varying degrees in both groups after surgery, and SAI value of angle scleral margin incision group in 1wk and 1mo postoperatively was significantly lower than that in clear corneal incision group(P<0.05). The corneal astigmatism at 1wk postoperatively was significant increased in both groups(P<0.05). The astigmatism increase of clear corneal incision group at 3mo postoperatively was still higher than that before surgery.CONCLUSION: Angle scleral margin incision has less effect on stability of tear film and corneal surface morphology, which is reliable on phacoemulsification.